2015
DOI: 10.15294/kemas.v11i1.3464
|View full text |Cite
|
Sign up to set email alerts
|

Pengetahuan, Sikap Dan Pencegahan Hiv/Aids Pada Ibu Rumah Tangga

Abstract: Cases of Human Immunodeficiency Virus (HIV) infection in Pati District increase, particularly among housewives. The aim of this study was to analyse the risk factors of HIV infection among housewives in Pati District using case-control study design. The respondents were 90 housewives divided into case and control group. The case group consisted of 30 housewives living with HIV, while the control group comprised 60 housewives living in the similar area of the counterparts. The data collection was focused on dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 1 publication
0
4
0
5
Order By: Relevance
“…Several studies have been conducted concerning HIV/AIDS prevention [ 23 , 24 ], while scarce literature addresses socio-economic and demographic factors associated with knowledge and attitudes toward HIV/AIDS in Indonesia. Knowledge and attitudes concerning HIV/AIDS among Indonesian women remain critical concerns as some studies revealed insufficient knowledge and negative attitudes [ 25 , 26 , 27 ]. Further, recent studies regarding the knowledge and attitudes of HIV/AIDS in Indonesia reemphasized that behavioral issues remain a challenge [ 9 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted concerning HIV/AIDS prevention [ 23 , 24 ], while scarce literature addresses socio-economic and demographic factors associated with knowledge and attitudes toward HIV/AIDS in Indonesia. Knowledge and attitudes concerning HIV/AIDS among Indonesian women remain critical concerns as some studies revealed insufficient knowledge and negative attitudes [ 25 , 26 , 27 ]. Further, recent studies regarding the knowledge and attitudes of HIV/AIDS in Indonesia reemphasized that behavioral issues remain a challenge [ 9 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Talcott Parsons stated there should be at least two or more personnel and interaction between them in service system, purposefulness, structure, symbol and mutual expectation to which it refers (Torpey, 2011;Octavianty 2015). This system provides conceptual framework to interact between fellow human beings in a variety of situations, established by norms, trust, and values organized with role expectation.…”
Section: Methodsmentioning
confidence: 99%
“…Fenomena gunung es kasus HIV AIDS yang terjadi di Indonesia disebabkan terdapatnya sedikit kasus yang terlapor dibandingkan dengan angka kejadian pada kondisi yang sebenarnya (Octavianty et al, 2015). Peningkatan kasus sejak tiga dekade terakhir dari pelaporan resmi pada tahun 1987.…”
Section: Pendahuluanunclassified